Pengaruh Jenis Kelamin, Promosi Penjualan dan Sifat Materialisme terhadap Perilaku Impulse Buying Secara Online - Chandra, I Komang Agus Hari; Purnami, Ni Made (E-Jurnal Manajemen; Vol 3 No 8 (2014), 2014)
The aim of this study is to examine and analyze the influence of gender, sales promotion and the characteristic of materialism against the behavior of impulse buying via online. This research was conducted by regular students of faculty of Economics and Business, Udayana University who ever made purchasing via online. 98 correspondents were chosen in order to complete the data source by using purposive sampling method. The data was collected by using questionnaires which used 5-point likert scale to measure 14 indicators. Folded linear regression was used during the process of analyzing the data. The findings in this study show that gender variables significantly affect the behavior of impulse buying via online, where men mostly appeared in conducting impulse buying via online compared to women. Sales promotion variables and the characteristic of materialism significantly played an important role against impulse buying behavior via online. The implication of the result this study was pointed at the providers of online sales to provide more products related to men’s needs, provide discounts and they are expected to show the products in the forms of pictures or vidios in order to show the benefits that will be obtained by the consumers after having or consuming those products.
Keywords: Gender, Sales Promotion, Materialism, Impulse Buying